1995
DOI: 10.1063/1.358641
|View full text |Cite
|
Sign up to set email alerts
|

Kr incorporation in sputtered amorphous Si layers

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. Amorphous Si layers were grown by krypton plasma sputter deposition at 310 'C. By pulsation of the substrate potential between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…These are, in turn, widely different to the results obtained for the crystalline material, which is in the region of 18% lower than the amorphous layer. This is in accordance with previous studies on the comparative hardness and elastic modulus of crystalline and amorphous materials [16]. Any slight deviation from this expected difference can be accounted for in the fact that the matrix of the crystalline material has a very fine eutectic structure, which is reflected in the ease with which it forms an amorphous matrix as stated previously.…”
Section: Hardness and Scratch Observationssupporting
confidence: 93%
“…These are, in turn, widely different to the results obtained for the crystalline material, which is in the region of 18% lower than the amorphous layer. This is in accordance with previous studies on the comparative hardness and elastic modulus of crystalline and amorphous materials [16]. Any slight deviation from this expected difference can be accounted for in the fact that the matrix of the crystalline material has a very fine eutectic structure, which is reflected in the ease with which it forms an amorphous matrix as stated previously.…”
Section: Hardness and Scratch Observationssupporting
confidence: 93%
“…An unsatisfactory aspect of the Mössbauer measurements of Greuter et al [1] is the fact that the data did not show any temperature dependence of the recoilless fraction, only fluctuations due to a varying peak-background ratio. We therefore decided to repeat these measurements and to study also the Kr concentration dependence.…”
Section: Introductionmentioning
confidence: 92%
“…It is therefore of interest to study the incorporation process and the sites of noble-gas atoms in amorphous and crystalline Si. Recently Greuter et al [1,2] reported on a detailed study of 0.5-6 at.% Kr in a-Si films grown by plasma sputter deposition, using high-resolution electron microscopy (HREM), x-ray microanalysis, Rutherford backscattering (RBS), positron beam analysis, Raman spectroscopy, Mössbauer spectroscopy and bending measurements. There is a clear indication that ion-assisted growth leads to a strong reduction of open volume and that krypton resides in small agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…[ Additionally, the detector's imaging capability will allow for the localization of the site of a double β decay candidate within tens of µg's of selenium in a detector module. Following the double β decay of 82 Se, the 82 Kr daughter will remain essentially immobile [39]. Its selective removal and detection by single atom counting [40][41][42] may be possible and may offer an independent confirmation of double β decay.…”
Section: Further Improvementsmentioning
confidence: 99%